Formation of the Digital Economy in Uzbekistan and its Indicators - Saatova L. E. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This article is about the digital economy, which is the most hot topic today. The signs, indicators, and assessment of the digital economy, as well as its share in GDP are also cited.